Women’s Roles in Aboriginal Australian and Talang Mamak Literary Works: A Comparative Analysis - Aris, Qori Islami; Syam, Essy (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
This research conducts a comparative analysis of the representation of women’s roles in the Aboriginal society of Australia and the Talang Mamak society in Riau Province, Indonesia, through the literary works "Alinta, The Flame" by Hyllus Maris and Sonia Borg, and "Behuma" by Gunawan. The study aims to contribute to understanding gender dynamics in Indigenous communities, addressing the need for more inclusive perspectives on cultural preservation and women’s empowerment. Using a comparative literary analysis approach informed by anthropological perspectives, this study explores the similarities and differences in women’s domestic and public roles, their contributions to food production, and the cultural and social contexts shaping gender dynamics within these indigenous communities. The findings reveal that while there are shared responsibilities in the domestic sphere, there are distinctions in women’s participation in the public realm, reflecting unique cultural practices and the division of labor. However, in both communities, women’s domestic and public roles are intertwined, affirming their holistic contributions to ensuring the sustainability of their societies. This research highlights the importance of women’s roles in preserving cultural heritage and the need to recognize their contributions in both domestic and public spheres. By bridging literary representations with anthropological perspectives, this study offers insights into the complexities of gender roles in indigenous societies, contributing to discussions on cultural preservation and gender equality in diverse cultural contexts.